"Historical Formation and Modeling Principles of Uzbek Women's National Dress" - Gaybullaeva, Yulduz (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, a comprehensive study of the national clothes of Uzbek women from the 19th to the 20th centuries, their commonality and uniqueness, the process of formation and changes of traditional clothes, and the reasons for the emergence of modern national clothes are given.